Evaluation of Protective Efficacy of the Synthetic Peptide Vaccine Containing the T-Helper 1 Epitope with Cpg Oligodeoxynucleotide against Feline Infectious Peritonitis Virus Infection in Cats. Issue 7 (October 2014) - Takano, Tomomi; Tomizawa, Keisuke; Morioka, Hiroyuki; Doki, Tomoyoshi; Hohdatsu, Tsutomu
Background: Feline infectious peritonitis (FIP) is a feline coronavirus-induced fatal disease in domestic and wild cats. Cellular immunity is considered to play an important role in the prevention of FIP. Thus, induction of the cellular immune response is essential in vaccines against FIP virus (FIPV) infection. Methods: We immunized cats with peptides containing T-helper (Th)1 epitopes derived from the nucleocapsid (N) protein of the type I FIPV KU-2 strain (NP7 and NP8 ) with feline CpG-oligodeoxynucleotides (fCpG-ODNs) as a vaccine adjuvant. Results: Prevention against type II FIPV 79-1146 strain-induced FIP was slightly better in specific pathogen-free cats treated with NP7 and NP8 with fCpG-ODNs. However, immune tolerance was suggested to be induced by the high dose and frequency of NP7 and NP8 with fCpG-ODNs. Conclusions: Further investigations on the combination and concentrations of the peptides and fCpG-ODNs, dose, frequency and route of administration are needed.